Are Emotional and Behavioral Problems of Infants and Children Aged Younger Than 7 Years Related to Screen Time Exposure During the Coronavirus Disease 2019 Confinement? An Exploratory Study in Portugal - Monteiro, Rita; Rocha, Nuno Barbosa; Fernandes, Sandra (Frontiers in Psychology, 2021)
The COVID-19 outbreak forced most of the world population to be confined at home to prevent contagion. Research reveals that one of the consequences of this confinement for children is an increased amount of the time spent using screens (television, computers, mobile devices, etc.) at home. This exploratory study aims to analyze the association between screen time exposure and emotional/behavioral problems of infants and children aged under 7 years, as manifested during the lockdown period in Portugal due to the COVID-19 outbreak. The study controlled for sociodemographic and confinement variables. A sample of 193 parents of children aged from 6m to 6y12m, residing in Portugal, completed a survey about the time and manner of use of screen time exposure of their children. Data were derived on circumstances both before and after the confinement; the survey also explored the child’s behavioral and emotional adjustment. The findings revealed a modest relationship between children’s exposure time to screens and behavioral and emotional problems on children studied. It was also found that parents may play an important role in children’s behavioral and emotional adjustment during the confinement period.